Genetic polymorphism of the human organic solute carrier protein 1 (hOSCP1) gene in Japanese patients with non-viral liver carcinoma - Toda, Mayumi (Meta Gene, 2014)
Human organic solute carrier protein 1 (hOSCP1) is a Na(+)-independent multispecific organic solute transporter. To date, several studies have revealed that gene mutations of the transporters are likely to be associated with some diseases; however, there are no data concerning the genetic polymorphism of the hOSCP1 gene in Japanese patients with non-viral liver carcinoma (LC). In the present study, we isolated genomic DNA from a normal portion of LC, and analyzed 41 single nucleotide polymorphisms (SNPs) chosen from a database of SNPs (dbSNPs). We found genotype frequencies for 2 non-synonymous SNPs [rs34409118 (Thr(131) → Ala) and rs1416840 (Ile(219) → Thr)] and 1 synonymous SNP [rs16822954 (Ser(193) → Ser)] to be statistically significant when compared with dbSNPs. No statistical significance was observed in rs2275477 (Gly(307) → Arg) in the hOSCP1 gene. With respect to the allele frequency, we also observed rs34409118 to be statistically significant. Interestingly, we found that non-viral LC patients do not carry heterozygous mutations in rs1416840 (A/G) and rs16822954 (A/G), suggesting that a non-carrier of heterozygous mutations in these two SNPs might be a biomarker for susceptibility for non-viral LC in Japanese. Further analyses of patients with hOSCP1 variants may elucidate the relationship between the hOSCP1 gene and susceptibility of non-viral LC in Japanese patients.